The Restoration of the Paintings of Le Corbusier in the Villa E-1027, Roquebrune-Cap-Martin, Alpes Maritimes - Hubert, Marie-Odile (Docomomo Journal, 2015)
The restoration of the paintings of Le Corbusier in the Villa E-1027 was preceded by an important study phase including systematic sampling of the paintings. One purpose of the study was to determine the presence of the original paintings under the global over-paint made by a local craftsman in the seventies. Four of the eight paintings have been rediscovered, in a much better condition than expected. These paintings are a fragile testimony of the particular use of “Ripolin” by Le Corbusier, in the context of its use by others famous artists as Picasso or Picabia in the same period.